2018
DOI: 10.1177/1609406918768014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing Qualitative Research

Abstract: Systematic synthesis of qualitative studies is widely used in health and social care. Regardless of the topic area, researchers need to consider several decisions when it comes to the planning and implementation of qualitative synthesis. As junior reviewers, we reflect on potential challenges and pitfalls in planning and conducting a synthesis of qualitative evidence. This article aims to elaborate on a number of key issues in order to provide insights and options on how to avoid or minimize these issues, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 51 publications
0
29
0
2
Order By: Relevance
“…Eight (21%) studies were randomly selected and double coded to check for consistency. 31 The team also met to compare their codes, discuss discrepancies, and refine their codes based on consensus. All coding and syntheses were conducted manually and recorded in Microsoft Excel.…”
Section: Data Extraction and Codingmentioning
confidence: 99%
“…Eight (21%) studies were randomly selected and double coded to check for consistency. 31 The team also met to compare their codes, discuss discrepancies, and refine their codes based on consensus. All coding and syntheses were conducted manually and recorded in Microsoft Excel.…”
Section: Data Extraction and Codingmentioning
confidence: 99%
“…Challenges regarding the systematic review of qualitative data will be overcome by making use of the key considerations proposed by Soilemezi and Linceviciute (46). The heterogeneity across studies will be assessed by generating a table of similarities and differences of developed themes across different studies.…”
Section: Meta-biasmentioning
confidence: 99%
“…This could have led to inclusion of more studies from the peer-reviewed literature giving a wider range of experiences, however, this review specifically focused on studies that explicitly identified Muslim women, reflecting calls for more research to consider women's religious identity. In addition, broadening the scope may have compromised the review being manageable [50].…”
Section: Strengths and Limitationsmentioning
confidence: 99%